Crowdsourcing of Inventive Activities, AI, and the NIH Syndrome - Thierry Burger-Helmchen (Administrative Sciences)
This study examines how crowdsourcing can support innovation in companies. It focuses on the Not Invented Here (NIH) syndrome—a reluctance to adopt external ideas—that varies depending on which organizational boundaries are considered, such as power, competence, and culture. By analyzing how these boundaries influence resistance to crowdsourced solutions, this study finds that although crowdsourcing brings valuable diversity and insights, many organizations struggle to leverage these effectively. Moreover, with the rise of generative AI, many organizations are increasingly focused on internal data and AI-driven innovation, which further intensifies NIH syndrome by deprioritizing external insights. We discuss why and how companies that have managed NIH syndrome effectively may be better positioned to overcome resistance to AI.